2023
DOI: 10.1080/0886022x.2023.2202756
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled comparative study of different fluid exchange modes in urgent-start peritoneal dialysis in patients with end-stage renal disease: automated peritoneal dialysis combined with manual fluid exchange vs. manual fluid exchange alone

Abstract: During urgent-start peritoneal dialysis (USPD) in end-stage renal disease (ESRD) patients, both adequate dialysis and skill training for fluid exchange are essential. However, automated peritoneal dialysis (APD) alone or manual fluid exchange peritoneal dialysis (MPD) alone could meet the above demands. Therefore, our study combined APD with MPD (A-MPD), and compared A-MPD with MPD, aiming to find the most appropriate treatment mode. This was a single-center, prospective, randomized controlled study. All eligi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Two studies investigated the outcomes of patients prescribed APD, CAPD, or combination APD-CAPD in patients requiring USPD, where patients began on APD for 3 days and then switched to CAPD. Both studies demonstrated that combination APD-CAPD is superior at removing small-molecule toxins and correcting electrolyte imbalances [21,22]. In one of these studies, the APD-alone group demonstrated decreases in serum albumin that were not shown in the APD-CAPD group, suggesting that CAPD may be suggestive against protein loss.…”
Section: Peritoneal Dialysis Prescription and Modality Choicesmentioning
confidence: 98%
“…Two studies investigated the outcomes of patients prescribed APD, CAPD, or combination APD-CAPD in patients requiring USPD, where patients began on APD for 3 days and then switched to CAPD. Both studies demonstrated that combination APD-CAPD is superior at removing small-molecule toxins and correcting electrolyte imbalances [21,22]. In one of these studies, the APD-alone group demonstrated decreases in serum albumin that were not shown in the APD-CAPD group, suggesting that CAPD may be suggestive against protein loss.…”
Section: Peritoneal Dialysis Prescription and Modality Choicesmentioning
confidence: 98%